Implementation of video learning media in Islamic Religious Education subjects for Elementary School Students - Azizah, Silva Nurul; Nandiyanto, Asep Bayu Dani; Wulandary, Verra; Irawan, Asep Rudi (Universitas Pendidikan Indonesia (UPI), 2022)
The development of technology in the world of education brings various positive and negative impacts. In connection with this, the use of technology in learning in the modern era has led to various kinds of innovations, one of which is the use of video as a medium of learning in Islamic Religious Education subjects. The purpose of this research was to determine the implementation of video learning media in the subject of Islamic Religious Education. This research was conducted with quantitative methods, collecting data obtained from filling out pre-test and post-test questionnaires to students at SD IT YASIFA. The results showed an increase after being given a learning video. Based on this, the research found findings that the implementation of video as a learning medium received a good response from teachers and students, one of which was an interesting activity. However, not all teachers can make these video learning media independently, and these media often produce unstable audio and low resolution, causing the student learning process to be uncomfortable.